Linking words and inferential analysis in primary school - Pestana Velandia, Lisbeth Nataly; Martínez Ferro, Hernán (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
The inference is a logical-cognitive process that allows us to arrive at a proposition taking into account as an initial basis, other given propositions. Therefore, it allows creating relationships or connections between meanings in a set of propositions. Inferential reading is an essential moment in the process that leads critical reading, to the point that it can be said that without inferential reading, critical reading cannot be done. Based on the previous postulate, this research focused on strengthening inferential analysis, from the use of discursive connectors in argumentative texts, with third-grade children. For this reason, three connectors of the discourse were chosen: “because”, “however” and “also”. With them, it was intended that the student familiarize himself and understand the meaning of each one, and when using them appropriately, allow them to understand the structure of an argument and easily identify the functions that fulfill the premises and conclusions within it. A proposal was implemented under the interpretive paradigm with a mixed research approach, through the application of didactic units. The results showed a greater use of the connectors as a guide to make inferences, likewise, they facilitated the identification of premises and conclusions, leading to the creation of their own arguments with a logical relationship.